2018
DOI: 10.1111/jcpp.12901
|View full text |Cite
|
Sign up to set email alerts
|

When repetitive mental sets increase cognitive flexibility in adolescent obsessive–compulsive disorder

Abstract: The study shows that cognitive flexibility can be better in OCD than controls. This may be the case in situations where superior abilities in the reactivation of repeating mental sets and difficulties to process new ones coincide. This may be accomplished by intensified inhibitory control mechanisms. The results challenge the view on OCD, since OCD is not generally associated with cognitive inflexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 47 publications
(72 reference statements)
0
37
1
Order By: Relevance
“…This region is wellknown to play a central role in inhibitory control processes (e.g., Aron, Monsell, Sahakian, & Robbins, 2004;Bodmer & Beste, 2017;Dippel & Beste, 2015;Stock, Popescu, Neuhaus, & Beste, 2016) and has previously been shown to be associated with inhibitory gating processes reflected by the P1 during backward inhibition (Wolff et al, 2018). The larger P1 in the nth trial of the BI compared with the BASE condition therefore suggests that the suppression of the inhibitory effect of the n-1 trial on the n-2 trial is stronger in the BI condition.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This region is wellknown to play a central role in inhibitory control processes (e.g., Aron, Monsell, Sahakian, & Robbins, 2004;Bodmer & Beste, 2017;Dippel & Beste, 2015;Stock, Popescu, Neuhaus, & Beste, 2016) and has previously been shown to be associated with inhibitory gating processes reflected by the P1 during backward inhibition (Wolff et al, 2018). The larger P1 in the nth trial of the BI compared with the BASE condition therefore suggests that the suppression of the inhibitory effect of the n-1 trial on the n-2 trial is stronger in the BI condition.…”
Section: Discussionmentioning
confidence: 89%
“…The same electrode site showing a P1 effect in backward inhibition has recently been used (Wolff et al, 2018 For the target N2 (Figure 3c), the mixed effects ANOVA revealed no significant main or interaction effects (all F < 1.56, p > .219). The mixed effects ANOVA for the target P3 ( Figure 3d) To summarize, the analysis of standard ERP components did not reveal interactive effects between BI/BASE condition and group.…”
Section: Standard Event-related Potentials (Erps)mentioning
confidence: 95%
See 3 more Smart Citations